DISTURBED HOMEOSTASIS OF SOME INORGANIC ELEMENTS ASSOCIATED WITH CHRONIC EXPOSURE TO LOW LEVELS OF BENZENE AND POSSIBLE ASSOCIATED HEALTH HAZARDS - Kotb, MA; Ramadan, HS; Shams El-Din, RS.; El-Bassiouni, EA; Refaat, R. (European Scientific Journal, ESJ, 2014)
Objective: Moderate and long-term exposures to benzene carry the risk of numerous health problems. Involvement of inorganic elements in such hazards has been suggested, but their role in problems resulting from occupational exposure to low-level benzene has not been reported. Methods: An all male cohort of 60 healthy control subjects and 180 individuals occupationally chronically exposed to low levels of benzene in their daily activity was enrolled in the study. Nineteen elements were determined in plasma and RBCs. Results: Higher levels of lead, mercury and cadmium were found in the plasma and RBCs of benzene-exposed workers, while the levels of zinc, selenium and copper were lower. Cobalt showed only a small but significant increase. There were no significant differences between other assayed elements in exposed workers and control subjects. Exposure to benzene was found to cause oxidative stress with significant elevation of plasma MDA level and decrease in total antioxidant activity. There was also a tendency for a higher degree of hemolysis in blood samples. Conclusion: All of the accumulated metals are proposed to contribute to oxidative stress by different mechanisms. They are either redox-active, directly involved in the production of free radicals, or are redox-inert, and contribute to oxidative stress by inhibiting antioxidant defense. The effect of excessive production of free radicals on RBCs membrane may explain the tendency for hemolysis in blood samples from benzene-exposed subjects. Metals with decreased concentrations may cause other metabolic disturbances and accelerate free radical production, probably through decreased participation in antioxidant protection.